Assessing universality of DNA barcoding in geographically isolated selected desert medicinal species of Fabaceae and Poaceae - Tahir, Aisha; Hussain, Fatma; Ahmed, Nisar; Ghorbani, Abdolbaset; Jamil, Amer (PeerJ, 2018)
In pursuit of developing fast and accurate species-level molecular identification methods, we tested six DNA barcodes, namely ITS2, matK, rbcLa, ITS2+matK, ITS2+rbcLa, matK+rbcLa and ITS2+matK+rbcLa, for their capacity to identify frequently consumed but geographically isolated medicinal species of Fabaceae and Poaceae indigenous to the desert of Cholistan. Data were analysed by BLASTn sequence similarity, pairwise sequence divergence in TAXONDNA, and phylogenetic (neighbour-joining and maximum-likelihood trees) methods. Comparison of six barcode regions showed that ITS2 has the highest number of variable sites (209/360) for tested Fabaceae and (106/365) Poaceae species, the highest species-level identification (40%) in BLASTn procedure, distinct DNA barcoding gap, 100% correct species identification in BM and BCM functions of TAXONDNA, and clear cladding pattern with high nodal support in phylogenetic trees in both families. ITS2+matK+rbcLa followed ITS2 in its species-level identification capacity. The study was concluded with advocating the DNA barcoding as an effective tool for species identification and ITS2 as the best barcode region in identifying medicinal species of Fabaceae and Poaceae. Current research has practical implementation potential in the fields of pharmaco-vigilance, trade of medicinal plants and biodiversity conservation.
Keywords: DNA barcoding; Medicinal plants; Ribulose bisphosphate carboxylase large chain (rbcLa); Species identification; Maturase k (matK); Internal transcribed spacer region (ITS2); Combination barcodes